Association between Visual Impairment and Socio-Economic Factors in Karachi Population - Arbaz Riaz, Ashar Shah, Saba Alkhairy, Zahra Turab (Pakistan Journal of Ophthalmology, 2017)
Purpose: To determine a correlation between visual impairment and socioeconomic levels within the eye outpatient department (OPD) of Dow University Hospital, Ojha Campus, Karachi, Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Dow University Hospital Eye OPD, Karachi, From January 11th 2016 to August 5th 2016. Material and Methods: A detailed history of each patient was first obtained, followed by an initial test for visual acuity and refraction by an optometrist using Snellen’s chart and Auto Refractometer RM 8800, Model: 2005 TopCon. After dilating with 1% tropicamide solution, the anterior/posterior segments were evaluated. The evaluation was performed by an Ophthalmologist, who later subdivided the patients. Each patient were subdivided based on a modified WHO categorization of visual impairment.1Patients were organized into three groups; mild at 6/9 to 6/12, moderate at 6/18 to 6/24, and severe at 6/36 to 6/60. Results: Among 350 patients, 182 (52%) were males and 168 (48%) were females. The mean age was 54.71 ± 11.83 years. A majority of patients had mild visual impairment (n = 257, 73.4%) whereas 43 (12.3%) had severe visual impairment. Socio-demographic characteristics such as age and education level were found to be significantly associated with visual impairment (p-value = 0.002) and (p-value = 0.024), respectively. Conclusion: The results show a direct correlation between visual impairment and socioeconomic factors such as education, gender, and ethnicity.